Development of the Thai version of Mini-Cog, a brief cognitive screening test - Trongsakul,S. (Japan Geriatrics Society, 2015)
© 2014 Japan Geriatrics Society. Aims: Cognitive impairment, such as dementia, has emerged as the leading public health problem among the elderly. Therefore, early detection of the disorder and providing appropriate healthcare and management is important, particularly, for the patients with comorbid diabetes who require long-term treatment strategies. In Thailand, because of a large number of elderly patients with diabetes, and time constraints in primary care settings, a short and effective cognitive screening test is required. The Mini-Cog is a short and valid cognitive screening test that was specifically designed for use in primary care settings. The present study translated the English language version into a Thai language version, and then measured the interrater reliability and concurrent validity. Methods: The processes of cross-language translation were carried out to develop a Thai language version of the Mini-Cog. A total of 21 Thai older adults with type2 diabetes with a mean aged of 69±7years were recruited into a study investigating the interrater reliability and concurrent validity of the Mini-Cog Thai version in one primary care center in Thailand. Results: The Mini-Cog Thai version showed a good interrater reliability (K=0.80, P<0.001, 95% CI 0.50-1.00) and a positive concurrent validity (r=0.47, P=0.007, 95% CI 0.37,0.55) with the Mini-Mental State Examination Thai 2002. Conclusions: The findings show that the Thai version of the Mini-Cog is a reliable, performance-based tool in the screening for cognitive function in primary care settings in Thailand. It is recommended that it could be used as a new cognitive screening test for the aging population in the Thai community.